2015
DOI: 10.3390/e17106801
|View full text |Cite
|
Sign up to set email alerts
|

On the Calculation of System Entropy in Nonlinear Stochastic Biological Networks

Abstract: Abstract:Biological networks are open systems that can utilize nutrients and energy from their environment for use in their metabolic processes, and produce metabolic products. System entropy is defined as the difference between input and output signal entropy, i.e., the net signal entropy of the biological system. System entropy is an important indicator for living or non-living biological systems, as biological systems can maintain or decrease their system entropy. In this study, system entropy is determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 65 publications
0
20
0
1
Order By: Relevance
“…PPIs have revealed global topological and dynamic features related to well-understood biological properties [ 20 ]. This indicates that studying PPIs will allow further understanding of disease mechanisms at a systematic level [ 21 - 23 ]. Wang et al identified C. albicans -zebrafish interspecies PPIs and used this information to highlight the association between C. albicans pathogenesis and the zebrafish redox process, indicating that redox status is critical in the battle between the host and pathogen [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…PPIs have revealed global topological and dynamic features related to well-understood biological properties [ 20 ]. This indicates that studying PPIs will allow further understanding of disease mechanisms at a systematic level [ 21 - 23 ]. Wang et al identified C. albicans -zebrafish interspecies PPIs and used this information to highlight the association between C. albicans pathogenesis and the zebrafish redox process, indicating that redox status is critical in the battle between the host and pathogen [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the configuration of its attractor (in deterministic case) or confiner (in random case) landscape in the network state space, it is related to the richness of the network attractor or confiner landscape [ 11 ]. The literature on network entropies is abundant [ 19 , 20 , 21 , 22 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ] and concerns both discrete or continuous dynamical systems, which share common mathematical concepts, such as attractor, attraction basin, Jacobian interaction graph, stability and robustness. We take as the definition of an attractor, that given in [ 63 , 64 ], available for both continuous and discrete cases.…”
Section: Methodsmentioning
confidence: 99%
“…The indirect entropy measurement method we proposed can deal with the nonlinear stochastic continuous systems. Though the study in [24] is about the continuous nonlinear stochastic system, many physical systems are always modeled using stochastic partial differential dynamic equation in the spatio-temporal domain. The indirect entropy measurement method we proposed can be employed to solve the system entropy measurement in nonlinear stochastic partial differential system problem.…”
Section: Bypx Tqmentioning
confidence: 99%
“…Therefore, if system randomness can be measured, the system entropy can be easily obtained from its logarithm. The system entropy of biological systems modeled using ordinary differential equations was discussed in [24]. However, since many real physical and biological systems are modeled using partial differential dynamic equations, in this study, we will discuss the system entropy of SPDSs.…”
Section: Introductionmentioning
confidence: 99%